(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Women once veneratedas the mother and the perpetuating angel of mankind has come to be looked uponas ’the unblessed creature of God’ in India, thanks to the club-and-dragcave-man attitude of the traditionally male-dominated society. Thelatest gang rape in Delhi has stirred the conscience of the nation. It hascreated ripples in the corridors of power and furore in the society in general.Even various international forums like U.N. Human Rights bodies andorganization working for women have expressed deep concern over the heinousact, the brutality involved and the pathetic attitude of the society andextreme pain of the victims who were lying injured and in semi nude conditionon the road side and no body from the so called civilized society came forwardto provide necessary help to the victims. When the police came it also gotentangled in the question of jurisdiction of police stations and tried to coldshoulder the issue. The public outcry afterwards, the unprofessional attitudeof the police and the mishandling of the public stir by Delhi Police has putDelhi Police under scanner. The whole “Show” highlighted the impotency of thesociety at large and failure of the administrative system. The victim of thegang rape lost her life and the companion’s family decided to bid Delhi goodbye forever. Fastrack courts have been set up to deal with the cases of crimeagainst women. Now the mostimportant question is that whether this is the first instance of crime againstwomen, if no why we have not proper system in order to deal with such kind ofcases, further what are the reasons of such crime and whether our approach isto let the crime happen or to create such mechanism as to prevent theoccurrence of such crimes. There are certain big question marks on the wholesystem.